Synthesis and investigation of benzimidazole and carbazole ß-haematin inhibiting scaffolds with antimalarial activity - L'abbate, Fabrizio P (Department of Chemistry, 2018)
Chloroquine was one of the main malarial treatments until the late 1960s when resistance began to emerge. This antimalarial targets haemozoin formation which causes a cytotoxic accumulation of free haem in the malaria parasite leading to parasite death. This is still one of the most promising pathways for treatment of the most prevalent species of malaria parasite, Plasmodium falciparum to date but, owing to growing resistance to chloroquine and other current antimalarial drugs, there is a dire need for new drugs. One strategy is to investigate non-chloroquine haemozoin inhibitors. High-throughput screening (HTS) was previously used to investigate novel β-haematin (synthetic haemozoin) inhibitors with promising P. falciparum growth inhibition activities. Of the 144 330 compounds screened, two hit compounds were selected for investigation in this project with two different scaffolds, namely benzimidazole and carbazole indole. In order to preselect benzimidazole derivatives for synthesis, Discovery Studio and Pipeline Pilot where used in tandem to enumerate 325 728 in silico compounds. These were filtered according to predicted β-haematin inhibition activities, followed by predicted malaria parasite growth activities using previously developed models based on Bayesian statistics. The predicted active compounds were further subjected to an in silico aqueous solubility model and separated according to predicted solubility values however, only 68 out of the 35 124 active compounds showed moderate solubility whilst the rest were poorly soluble. From this data, eighteen compounds were chosen for synthesis with varying functional groups. Using the same Bayesian models, biological activities for seven fragment compounds derived from the benzimidazole hit compound were predicted. Six out of seven were predicted to be β-haematin inhibitors while five out of seven were predicted active against the malaria parasite growth inhibition model. Similar Bayesian predictions were carried out on the seven proposed carbazole indole compounds with three compounds predicted to be β-haematin inhibitors while six compounds were predicted to be active against the malaria parasite growth inhibition model. The eighteen benzimidazole compounds were synthesized using a two-step synthesis, via a condensation reaction using polyphosphoric acid (PPA), 4-aminobenzoic acid and o-phenylenediamine to form the primary amine benzimidazole intermediate after which ani acylation reaction with the appropriate acid chloride furnished the desired compounds. β-haematin inhibition analysis revealed a 78% hit rate compared to the Bayesian predictions which resulted in a 24-fold enrichment compared to random screening. SAR analysis revealed an activity trend related to the position of substituents on the ring system as follows: para < ortho < meta. The type of ring system was also investigated, with a trend of phenyl < furan < pyrrole < thiophene < pyridyl found. The fragment compounds were either purchased or synthesized via standard acylation conditions using acid chlorides or acetic anhydride with primary amines as before. β-haematin inhibition analysis showed all these compounds to be inactive at the 100 µM cut-off but these compounds were still carried through to the next stage of testing in spite of these results. Molecular docking was carried out on all eighteen benzimidazole compounds in Materials Studio using the (001) and (011) β-haematin crystal faces for adsorption, together with a modified CVFF force-field. This showed a correlation between adsorption energies of the (011) β-haematin crystal face with the experimental β-haematin inhibition values. This indicated that the (011) β-haematin crystal face was the most important for β-haematin inhibition. Analysis of the benzimidazole compounds and their π-π and hydrogen bonding interactions was performed. The number of π-π interactions were found to be important for β-haematin inhibition activity. Both sets of benzimidazole compounds were tested against the NF54 chloroquine sensitive malaria parasite using growth inhibition assays with a 50% hit rate shown for the benzimidazole compounds and a 71% hit rate for the fragment study leading to a 26-fold and 36-fold enrichments compared to random screening. SAR analysis of the benzimidazole compounds revealed a trend for activity in relation to substituent position of para ≈ ortho < meta and a ring system trend of phenyl < pyridyl < thiophene < furan < pyrrole. The benzimidazole compounds were further tested against the chloroquine resistant Dd2 P. falciparum strain which showed that disubstituted compounds were more active against this strain. Cellular haem fractionation studies revealed an increase in free haem and decrease in haemozoin confirming that haemozoin inhibition is the mode of action for the benzimidazole compounds. QSAR analysis of these compounds revealed a correlation between the -Log(P. falciparum IC50) which is also known as pLog(P. falciparum IC50) and 1/βhaematin IC50, number of hydrogen bond donors and molecular depth with 1/β-haematin IC50 the most dominant term. iv The first four carbazole indole compounds were synthesized using a two-step synthesis via deprotonation of carbazole and reaction with epichlorohydrin or 1,3-dibromopropane to furnish the epoxide or alkylbromine intermediates. These intermediates underwent a further SN2 reaction using deprotonated indole to furnish four final compounds. Synthesis of another three derivatives required benzyl protection of 7-hydroxyindole alcohol first, followed by reaction with the epoxide intermediates via an SN2 mechanism to furnish the final three compounds. Analysis using the turbidimetric solubility assay revealed the best aqueous solubility range of this series of compounds to be 10-20 µM (moderately soluble). β-haematin inhibition studies were carried out on this series of compounds with a 100% hit rate found when compared to the Bayesian model data which lead to 30-fold enrichment when compared to random screening. SAR analysis showed an increase in the number of hydroxyl groups led to an increase in β-haematin inhibition activity. Docking studies were performed on these seven compounds and showed that hydrogen bonding played a role in anchoring the molecules in the binding pocket on the crystal surface with increased adsorption energies seen with an increase in the number of hydroxyl groups. Malaria parasite growth inhibition studies showed no compounds to be active against the NF54 and Dd2 strains at the 2 µM cut-off. Cellular haem fractionation studies on the carbazole indole compounds showed that this series of compounds acts via a mechanism that results in inhibition of haemoglobin uptake into the food vacuole and not via haemozoin inhibition.